Hubungan Attitude toward Behavior, Subjective Norm, dan Perceived Behavioral Control dengan Intensi Melakukan Exercise pada Mahasiswa Universitas Indonesia - Pradipta Citra Safitri; Adhityawarman Menaldi (Fakultas Psikologi Universitas Pancasila, 2012)
The purpose of this research is to investigate the relationship among attitude toward behavior, subjective norm, and perceived behavioral control with exercise intention by utilizing campus facility in college students of Universitas Indonesia. One hundred and thirteen college students participated by filling out the questionnaire which measuring the intention and its determinant factor based on Theory of Planned Behavior. Those determinant factors are attitude toward behavior, subjective norm, and perceived behavioral control. The result indicates a significant relationship among attitude toward behavior, subjective norm, and perceived behavioral control is the most influencing factor on exercise intention by utilizing campus facility.